Podaż pracy w Polsce – dotychczasowe tendencje i projekcje na przyszłość - Kwiatkowski, Eugeniusz; Kucharski, Leszek (Studia Demograficzne, 2018)
The scope of the paper refers to long- and medium-run trends of labour supply in Poland. The main purpose is to determine current trends in the labour supply and its projections till the year 2050. In the theoretical part of the paper determinants of labour supply are considered. The projections are based on the population forecasts till 2050 made by the Central Statistical Office of Poland (CSO) and by the authors’ own simulations. Several variants of upper limit of working age and activity rates are taken into account. The population forecasts by the CSO indicate it will occur big decrease of working age population till 2050. The biggest decrease will refer to the group of working age 18–59/64 years and the lowest decrease in the age group 18–66 years. The analysis shows that the declines in labour supply in the years 2020–2050 will occur in all variants of working age population, the biggest decline in the variant assuming the age group 18–59/64 and the smallest decline – in the group 15–74 years. Retirement age is of big importance for the size of labour supply. This is why it is recommended to encourage older people to prolong their economic activity. It is also necessary to increase activity rates in the working age population.